The Impact of Green Marketing and Artificial Intelligence on Interest in Using the Grab Indonesia Application: Dampak Green Marketing dan Artificial Intelligence Terhadap Minat Penggunaan Aplikasi Grab Indonesia - Albert Nicholas; Desma Erica Maryati Manik (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
It is impossible to stop advances in technology; instead, they should be improved to make things easier for those who use technology. The quick rise of digital technology has caused big changes in many fields, like transportation and delivery services that use application. In Indonesia, Grab is one of the first companies to offer transportation, food delivery, and digital payment services. This research looks at how green marketing and artificial intelligence affect people's interest in using the Grab Indonesia application. People who had used Grab in the last 30 days made up the study group, with an unknown number, and a sample of 120 people was taken using Hair et al.'s method. The study's findings show that green marketing has some effect on people's interest in using Grab. According to the study's findings, using artificial intelligence has a partial impact on people's interest in using Grab. The research also shows that green marketing and artificial intelligence together affect people's interest in using Grab.